Skill obsolesence, vintage effects and changing tasks - Janssen, Simon [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2009)
"Human capital is no doubt one of the most important factors for future economic growth and well-being. However, human capital is also prone to becoming obsolete over time. Skills that have been acquired at one point in time may perfectly match the skill requirements at that time but may become obsolete as time goes by. Thus, in the following paper, we study the depreciation processes of the human capital of workers performing different types of tasks with different skill requirements over a period of more than twenty years. We argue that two types of tasks must be distinguished: knowledge-based tasks and experience-based tasks. Knowledge-based tasks demand skills depending on the actual stock of technological knowledge in a society whereas experience-based tasks demand skills depending on personal factors and individual experience values. We show, by applying Mincer regressions on four different cross sections, that the human capital of people performing knowledge-based tasks suffers more from depreciation than the human capital of individuals performing experience-based tasks." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.6 Human Capital; Humankapital; Qualifikationswandel; Wissensarbeit; Erfahrungswissen